2020
DOI: 10.3390/s20226533
|View full text |Cite
|
Sign up to set email alerts
|

Bicycling Phase Recognition for Lower Limb Amputees Using Support Vector Machine Optimized by Particle Swarm Optimization

Abstract: A novel method for recognizing the phases in bicycling of lower limb amputees using support vector machine (SVM) optimized by particle swarm optimization (PSO) is proposed in this paper. The method is essential for enhanced prosthetic knee joint control for lower limb amputees in carrying out bicycling activity. Some wireless wearable accelerometers and a knee joint angle sensor are installed in the prosthesis to obtain data on the knee joint and ankle joint horizontal, vertical acceleration signal and knee jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…In 2020, Li et al [16] proposed a unique approach for identifying bicycling stages in lower limb amputees utilizing a Support Vector Machine (SVM) enhanced by Particle Swarm Optimization (PSO). Wireless accelerometers then knee joint angle sensor in prosthesis collect information, filtered with a soft-hard threshold to reduce noise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2020, Li et al [16] proposed a unique approach for identifying bicycling stages in lower limb amputees utilizing a Support Vector Machine (SVM) enhanced by Particle Swarm Optimization (PSO). Wireless accelerometers then knee joint angle sensor in prosthesis collect information, filtered with a soft-hard threshold to reduce noise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…References Torque control for assisted E-bike [1,2,24,38,39] Instantaneous pedaling torque waveform [4][5][6][7] Pedaling torque component analysis [8][9][10][11][12][13][14] Factors affecting riding [15][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][32][33][34][35]] Recharge control for assisted E-bike [36,37] To overcome these limitations on existing E-bike assisted torque control, this paper's motivation is to find the best-suited assisted torque considering external loads. It is shown that the overall cycling torque is affected by external loads, including the cyclist's weight, wind resistance, rolling resistance, and the road slope.…”
Section: Categorymentioning
confidence: 99%
“…In [ 26 ], a comprehensive monitoring system was developed. This system integrates environmental factors [ 27 , 28 ], the cyclist’s heart rate [ 29 , 30 ] and respiratory rate [ 31 ], power consumption [ 32 ] and electromyogram [ 33 , 34 ] information, and journey time. Collecting data from the cloud can give the rider a reference indicator to determine the motor power of the journey in order to retain a longer battery life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them have lost their lower limbs due to natural disasters, traffic accidents and wars [1,2]. Currently, prostheses are the most significant tools to compensate for the walking function of lower-limb amputees [3][4][5][6][7]. However, most prostheses on the market, either passive or semiactive, cannot realize the joints' active swinging, and thus fail to achieve assisted walking [8].…”
Section: Introductionmentioning
confidence: 99%